Gender Discrimination and its Epistemological Basis: A Study on Feminist Epistemology (Philosophy and Progress, 2022)
The epistemology which we went through up to 1970’s has hardly been gender-sensitive, and with the emergence of feminism, mainly with its Second Wave, a group of gender-sensitive practitioners of epistemology and feminist philosophy came out to declare that our so far cultivated epistemology (which is sometimes regarded as “pure” and “standard‘) has subtly been infected with viruses of patriarchal ideology and androcentrism. Taking this gender dimension in mind, there has developed a considerable amount of literature, which is referred to as feminist epistemology. It is actually doing epistemology in order to assure cognitive justice to all, and thereby establish gendersensitive humanism, cleansing it from traditional androcentric biases and unjust patriarchal surveillance. This present article is a critical study of this feminist epistemology, where I shall be dwelling upon the epistemological roots of gender discrimination.Philosophy and Progress, Vol#69-70; No#1-2; Jan-Dec 2021 P 145-171